Advances in Friction, Lubrication, Wear and Oxidation in Metals Manufacturing - Deng, Guanyu; Zhu, Hongtao; Tieu, Anh Kiet (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a collection of the research papers published in the "Advances in Friction, Lubrication, Wear and Oxidation in Metals Manufacturing" Special Issue. It acts as an update on the state of the art concerning studies on friction, wear and oxidation properties of materials; the development and performance of novel lubricants; and advanced simulation strategies for friction contacts.